Wrist pain in young gymnasts: frequency and effects upon training over 1 year - DiFiori, J. P.; Puffer, J. C.; Aish, B.; Dorey, F. (Clinical Journal of Sport Medicine, 2002)
OBJECTIVE To determine the frequency and characteristics of wrist pain in young, nonelite gymnasts over a 1-year training period, and to describe the effects of chronic wrist upon gymnastics training. DESIGN Prospective cohort study. SETTING Los Angeles-based gymnastics club. PARTICIPANTS Forty-seven nonelite female and male gymnasts between 5 and 16 years of age. ASSESSMENTS Each subject completed an interview-based questionnaire and received a physical exam at the study onset and at the end of 1 year of training. The questionnaire detailed training habits and elicited a history and description of wrist pain. MAIN OUTCOME MEASURES The frequency of wrist pain and several measures of training were reported at the study onset and at 1 year. Gymnasts with wrist pain were compared with those who were pain-free. MAIN RESULTS Wrist pain was reported by 57% (27 of 47) of subjects at the study onset. Eighty-nine percent (24 of 27) reported wrist pain both at the study onset and 1 year later. Nineteen gymnasts (40%) were pain-free at each collection. The floor exercise, the pommel horse, and the balance beam were most frequently associated with wrist pain symptoms. Multivariate analysis revealed that adolescent gymnasts between 10 and 14 years of age were significantly more likely to report wrist pain at each survey than those who were either above or below this age range (p = 0.03). Forty-two percent of subjects with wrist pain at each survey reported that the symptoms interfered with training. Only five gymnasts with wrist pain were seen by physicians. Training intensity increased in gymnasts with and without wrist pain. The relative increase within each group was statistically significant among pain-free gymnasts (p = 0.003), but was not for those with wrist pain (p = 0.08). CONCLUSIONS Wrist pain among young, nonelite gymnasts is common, and appears to persist with continued training in the vast majority of those who report symptoms. Adolescent gymnasts between 10 and 14 years of age training at this level are significantly more likely to have wrist pain. Wrist pain appears to have a negative effect upon training, based upon both self-report and training intensity measures; however, more study is needed with respect to this issue.